IMPROVING THE PROFILE OF CHILDREN’S DENTAL ANOMALIES IN THE PERIOD OF CONSTANT TOOTH DECAY - A.A. Saidov; Muzaffarov B. Y. (Researchparks Publishing, 2022)
Тhere is no downward trend in the occurrence of tooth-jaw deformities in recent years, and growth in accordance with the age dynamics in these different pathological structures is noted. The opinions expressed by the researchers raise the issue of the need for a detailed study of the various types of tooth-jaw formations to determine the interdependence of these pathologies in all periods of tooth-jaw formation and the somatic state of the examined.